Struggle, Condemnation, Vindication : John Courtney Murray's Journey toward Vatican II - Hudock, Barry (Book collections on Project MUSE., 2015)
An account of the life and work of Fr. John Courtney Murray, who was first silenced by the Church, and subsequently vindicated at the Second Vatican Council. -- Back cover.